1993
DOI: 10.1111/j.1398-9995.1993.tb01107.x
|View full text |Cite
|
Sign up to set email alerts
|

Major allergens of date palm (Phoenix dactylifera L.) pollen

Abstract: The IgE-binding components of date palm (Phoenix dactylifera L.) pollen were determined by ELISA and Western blotting in atopic patients in order to identify its major allergens. From a pool of previously identified allergenic fractions and sera from 15 skin-test-positive, atopic subjects, four components of 12, 14.4, 57, and 65-67 kDa were found to bind IgE in 80-93% of sera. Two other components of molecular masses 28-30 and 37-40 kDa also bound 60-80% of atopic sera. The immunologic specificity of date-poll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 14 publications
2
16
0
Order By: Relevance
“…However, in that study only about 50% of patients’ sera bound IgE at 54–58 kDa. Studies on allergenicity of date palm pollen [3, 10, 12]and the present study on date fruits have all indicated that there are distinct differences in allergenicity and antigenicity of cultivars.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in that study only about 50% of patients’ sera bound IgE at 54–58 kDa. Studies on allergenicity of date palm pollen [3, 10, 12]and the present study on date fruits have all indicated that there are distinct differences in allergenicity and antigenicity of cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the dioecious nature of the date palm, and the long period of cultivation in areas where it is used as a food crop, the palm is heterozygous and has resulted in the establishment of hundreds of varieties or cultivars. The allergenicity of date pollen has been established [10]and the allergenic variability of pollen from different cultivars of the date palm has been elucidated [3]. Since then, differences in the allergenicity of cultivars of other plants such as olives [11]pecan, wild chenopods and some amaranths have been demonstrated [12, 13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sera derived from patients with skin prick test (SPT) were positive to highly allergenic cultivars as previously described [16]. …”
Section: Methodsmentioning
confidence: 99%
“…The existence of date palm cultivars which are differentially allergenic can create problems [12,13,14], making it difficult to devise precise in vitro and in vivo diagnosis, a factor which in turn creates gross underestimates of the real incidence of this kind of allergy [15]. The use of diagnostic extract prepared from highly allergenic cultivars which contain all major date pollen allergens is fundamental to identifying people affected by such a specific allergic disease and to develop a vaccine for specific immunotherapy [14, 16, 17]. …”
Section: Introductionmentioning
confidence: 99%